Medical glass container, film for medical glass container, and method for producing medical glass container

JP2025034746APending Publication Date: 2025-03-13AGC INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023141324
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0006】 本発明の医療用ガラス容器は、薬剤の保存安定性に優れる。 本発明の医療用ガラス容器用の膜によれば、薬剤の保存安定性に優れる医療用ガラス容器が得られる。 本発明の医療用ガラス容器の製造方法によれば、薬剤の保存安定性に優れる医療用ガラス容器が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034746000001_ABST
    Figure 2025034746000001_ABST
Patent Text Reader

Abstract

To provide a transparent medical glass container excellent in storage stability of drugs.SOLUTION: A medical glass container is provided, having: a main body which rises from the bottom and the periphery of the bottom and houses a drug; and a film which covers a surface of the container main body at least in the main body portion, the film includes an ultraviolet absorber, and the ultraviolet absorber consists of at least one organic ultraviolet absorber selected from the group consisting of triazine-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, azomethine-based ultraviolet absorbers, indole-based ultraviolet absorbers, benzodithiole-based ultraviolet absorbers, and oxazolone-based ultraviolet absorbers, and the value obtained by dividing the product of the thickness t1 (cm) of the film and the content c11 (mass %) of the ultraviolet absorber in the film by 100 (t1×c11 / 100) is 5.0×10-6 or greater.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a medical glass container, a membrane for a medical glass container, and a method for making a medical glass container. [Background technology]

[0002] Transparent glass packaging containers, such as glass vials, are widely used as pharmaceutical packaging containers (Non-Patent Document 1). [Prior art documents] [Non-patent literature]

[0003] [Non-Patent Document 1] “Vials | SCHOTT Pharma”, [online], schott-pharma.com, [Retrieved August 8, 2023], Internet<URL:https: / / www.schott-pharma.com / en / products / vials> Summary of the Invention [Problem to be solved by the invention]

[0004] However, conventional glass packaging containers do not provide sufficient storage stability for drugs, and depending on the type of drug, deterioration of the drug is observed during storage. The present invention provides a medical glass container having excellent storage stability for drugs, a film for a medical glass container which can provide a medical glass container having excellent storage stability for drugs, and a method for producing a medical glass container. [Means for solving the problem]

[0005] The present invention provides a medical glass container, a film for a medical glass container, and a method for producing a medical glass container, each having the following configurations [1] to

[15] . [1] A container body made of glass in which a medicine is contained, the container body having a bottom and a body part rising from the periphery of the bottom, and a film covering the surface of the container body at least in the body part; the film contains an ultraviolet absorber; the ultraviolet absorber is composed of at least one organic ultraviolet absorber selected from the group consisting of triazine-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, azomethine-based ultraviolet absorbers, indole-based ultraviolet absorbers, benzodithiol-based ultraviolet absorbers, and oxazolone-based ultraviolet absorbers; The product of the thickness t1 (cm) of the film and the content c1 (mass%) of the ultraviolet absorber in the film is divided by 100 (t1×c1 / 100), which is 5.0×10 -6 That's it for medical glass containers. [2] The medical glass container of [1], wherein the thickness t1 of the film is 1.0 to 10.0 μm. [3] A container body made of glass in which a medicine is contained, the container body having a bottom and a body part rising from the periphery of the bottom, and a film covering the surface of the container body at least in the body part; the film contains an ultraviolet absorber; the ultraviolet absorber is composed only of metal oxide particles, The product of the thickness t2 (cm) of the film and the content c2 (mass%) of the ultraviolet absorber in the film is divided by 100 (t2×c2 / 100), which is 1.78×10 -5 ~1.18×10 -3 That is, a medical glass container. [4] The medical glass container of [3], wherein the thickness t2 of the film is 1.0 to 5.0 μm. [5] The medical glass container according to [3] or [4], wherein the average particle size of the metal oxide particles is 1 to 500 nm. [6] A glass container body in which a medicine is contained, the glass container body having a bottom and a body part rising from the periphery of the bottom, A medical glass container, wherein the ultraviolet light transmittance measured at the body is 50% or less, and the visible light transmittance measured at the body is 60% or more. [7] A medical glass container according to any one of [1] to [6], wherein the yellowness index measured at the body position is 20 or less. [8] The medical glass container according to any one of [1] to [7], wherein the container body is a glass vial. [9] The medical glass container according to any one of [1] to [8], wherein the drug comprises an antibody-drug conjugate.

[10] Contains an ultraviolet absorber, the ultraviolet absorber is composed of at least one organic ultraviolet absorber selected from the group consisting of triazine-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, azomethine-based ultraviolet absorbers, indole-based ultraviolet absorbers, benzodithiol-based ultraviolet absorbers, and oxazolone-based ultraviolet absorbers; The product of the thickness t1 (cm) of the film and the content c1 (mass%) of the ultraviolet absorber in the film is divided by 100 (t1×c1 / 100), which is 5.0×10 -6 That is all about the membrane for medical glass containers.

[11] Contains an ultraviolet absorber, the ultraviolet absorber is composed only of metal oxide particles, The product of the thickness t2 (cm) of the film and the content c2 (mass%) of the ultraviolet absorber in the film is divided by 100 (t2×c2 / 100), which is 1.78×10 -5 ~1.18×10 -3 A membrane for medical glass containers.

[12] The film for a medical glass container according to

[10] or

[11] , which is formed from a composition containing the ultraviolet absorber and a matrix material.

[13] A method for producing a medical glass container, comprising applying a composition containing an ultraviolet absorber and a matrix material to at least a surface of a body of a glass container body in which a medicine is contained, the body having a bottom and a body rising from a peripheral edge of the bottom, to form a film, the ultraviolet absorber is composed of at least one organic ultraviolet absorber selected from the group consisting of triazine-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, azomethine-based ultraviolet absorbers, indole-based ultraviolet absorbers, benzodithiol-based ultraviolet absorbers, and oxazolone-based ultraviolet absorbers; The product of the thickness t1 (cm) of the film and the content c1 (mass%) of the ultraviolet absorber in the film is divided by 100 (t1 × c1 / 100), and the product is calculated as 5.0 × 10 -6 The above is a method for producing a medical glass container.

[14] A method for producing a medical glass container, comprising applying a composition containing an ultraviolet absorber and a matrix material to at least a surface of a body of a glass container body in which a medicine is contained, the body having a bottom and a body rising from a peripheral edge of the bottom, to form a film, the ultraviolet absorber is composed only of metal oxide particles, The product of the thickness t2 (cm) of the film and the content c2 (mass%) of the ultraviolet absorber in the film is divided by 100 (t2 × c2 / 100), which is 1.78 × 10 -5 ~1.18×10 -3 The method for manufacturing a medical glass container comprises the steps of:

[15] The method for producing a medical glass container according to

[13] or

[14] , wherein the matrix material comprises a curable silane compound, and the composition further comprises a catalyst and an aqueous medium. Effect of the Invention

[0006] The medical glass container of the present invention has excellent storage stability for medicines. According to the film for medical glass containers of the present invention, medical glass containers having excellent storage stability for medicines can be obtained. According to the method for producing a medical glass container of the present invention, a medical glass container having excellent storage stability for medicines can be obtained. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a vertical cross-sectional view showing an example of a medical glass container. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] In this specification, "ultraviolet rays" is also abbreviated as "UV." In this specification, the term "reactive silyl group" is a general term for a hydrolyzable silyl group and a silanol group (Si-OH), and the term "hydrolyzable silyl group" refers to a group that can form a silanol group by hydrolysis. "UV transmittance measured at the body position" is also referred to as "side UV transmittance." "Side UV transmittance" is the UV transmittance of one side. The "side" is the part of the body that separates the outside from the inside of a medical glass container. The side UV transmittance of medical glass containers is determined in accordance with ISO9050:2003. "Visible light transmittance measured at the body position" is also referred to as "side visible light transmittance." "Side visible light transmittance" is the visible light transmittance of one side. The side visible light transmittance of medical glass containers is determined in accordance with JIS R 3106:1998. "Yellowness index" is also abbreviated as "YI." "YI measured at the body position" is also referred to as "side YI." Side YI is calculated by the formula described in JIS K 7373:2006 using the tristimulus values ​​X, Y, and Z determined by the spectrophotometric colorimetric method specified in JIS Z 8722:2009. The symbol "~" indicating a range of values ​​means that the values ​​before and after it are included as the lower and upper limits. For ease of explanation, the scale of each part in the drawings may differ from the actual scale.

[0009] First Embodiment The medical glass container of the first embodiment comprises a glass container body in which a medicine is contained, the container body having a bottom and a body rising from the periphery of the bottom, and a membrane covering the surface of the container body at least in the body. The film contains a UV absorber. Therefore, the film has a UV shielding ability. Hereinafter, the film containing a UV absorber is also referred to as a "UV shielding film." UV blocking films typically contain a UV absorber in a matrix.

[0010] An example of the configuration of a medical glass container will be described with reference to FIG. The medical glass container 100 of this example has a glass vial 10 (container body) and a UV blocking film 20. The glass vial 10 has a bottom 11 and a body 12 rising from the periphery of the bottom 11. Above the body 12, a shoulder 13, a neck 14, and a mouth 15 are provided in this order from the body 12 side. Here, "upward" refers to the side opposite the bottom 11 side in the direction along the central axis of the glass vial 10. The shoulder 13 has a diameter that decreases toward the top. The neck 14 is formed in a cylindrical shape that is coaxial with the body 12 and has a smaller diameter than the body 12. The mouth 15 is formed in a cylindrical shape with an inner diameter equal to that of the neck 14 and an outer diameter larger than that of the neck 14. The UV blocking film 20 covers the outer surface of the glass vial 10 at the bottom 11, body 12, shoulder 13 and neck 14.

[0011] The container body may be any body having a bottom and a body rising from the periphery of the bottom, and is not limited to the glass vial 10 shown in Fig. 1. For example, the container body may be a glass vial or a glass ampule having a different shape from the glass vial 10 shown in Fig. 1. The UV shielding film may cover at least the body of the container body. The UV shielding film may cover the outer surface, the inner surface, or both the outer and inner surfaces of the container body. For example, the inner surface of the container body may not be covered with a film, the outer surface of the bottom of the outer surface of the container body may not be covered with a film, and the outer surfaces other than the bottom may be covered with a film. For example, the outer surface of the container body may not be covered with a film, the inner surface of the bottom of the inner surface of the container body may not be covered with a film, and the inner surfaces other than the bottom may be covered with a film.

[0012] The side UV transmittance of the medical glass container according to this embodiment is preferably 50% or less, more preferably 40% or less, even more preferably 30%, particularly preferably 15% or less, and most preferably 5% or less. When the side UV transmittance is equal to or less than the upper limit, UV incident on the medical glass container from the outside is sufficiently blocked, and the deterioration of the medicine contained in the container body due to UV can be suppressed, resulting in excellent storage stability of the medicine. The lower the side UV transmittance, the more preferable, and the lower limit is not particularly limited.

[0013] The side visible light transmittance of the medical glass container according to this embodiment is preferably 60% or more, more preferably 70% or more, even more preferably 80%, and particularly preferably 90% or more. When the side visible light transmittance is equal to or more than the lower limit, the state of the drug in the container body (for example, the presence or absence of aggregates in a liquid drug) can be easily visually confirmed from the outside. The higher the side visible light transmittance, the more preferable it is, and there is no particular upper limit.

[0014] The side YI of the medical glass container according to this embodiment is preferably 40 or less, more preferably 20 or less, even more preferably 10 or less, particularly preferably 5 or less, and most preferably 1 or less. When the side YI is equal to or less than the upper limit, the state of the drug in the container body (for example, the presence or absence of aggregates in a liquid drug) is easily visually observed from the outside. The lower the side YI, the better, and there is no particular limit to the lower limit.

[0015] (Container body) The glass constituting the container body may be any glass that is applicable to medical applications, and is typically borosilicate glass. The shape of the container body may be the same as that of known glass packaging containers such as a glass vial, a glass ampoule, a glass syringe, a glass screw bottle, etc. Glass vials and glass ampoules are preferred in terms of maintaining a sterile state.

[0016] The size of the container body may be similar to that of a known glass packaging container. In the case of a glass vial, the outer diameter of each of the bottom and body is, for example, 15 to 40 mm. The thickness of the body is, for example, 0.8 to 2.0 mm. The inner diameter of the mouth is, for example, 5 to 15 mm. The outer diameter of the mouth is, for example, 10 to 20 mm. The height of the glass ampoule is, for example, 30 to 80 mm.

[0017] The side UV transmittance of the container body varies depending on the thickness of the body, but is typically 90% or more. In the case of a typical borosilicate glass vial, it is about 90 to 98%.

[0018] The side visible light transmittance of the container body is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. When the side visible light transmittance of the container body is equal to or more than the lower limit, it is easy to make the side visible light transmittance of the medical glass container equal to or more than the preferable lower limit.

[0019] The side surface YI of the container body is preferably 10 or less, more preferably 5 or less, and even more preferably 3 or less. When the side surface YI of the container body is not more than the upper limit, it is easy to make the side surface YI of the medical glass container equal to or more than the preferable lower limit.

[0020] (UV shielding film) In the first embodiment, the UV absorbent contained in the UV shielding film consists of at least one organic UV absorbent selected from the group consisting of triazine-based UV absorbents, benzotriazole-based UV absorbents, benzophenone-based UV absorbents, azomethine-based UV absorbents, indole-based UV absorbents, benzodithiol-based UV absorbents, and oxazolone-based UV absorbents.

[0021] Examples of triazine-based UV absorbers include 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine, 2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine, 5-[3-(2-ethylhexyloxy)-2-hydroxypropoxy]-2-[4,6-bis(2,4-xylyl)-1,3,5-triazine-2-yl]phenol, 5,5'-dibutoxy-2,2'-[6-(2,4-dibutoxyphenyl)-1,3,5-triazine-2,4-diyl]diphenol, 4-[4-(6,1-diphenyl-3,5,2-triazin-3-yl)-2-hydroxyphenoxy]ethyl 2-ethylhexanoate, and Tinuvin manufactured by BASF. 477, Tinuvin 479, and Tinuvin 1600.

[0022] Examples of benzotriazole-based UV absorbers include 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-methylphenol, 2,2'-methylenebis[6-(benzotriazol-2-yl)-4-tert-octylphenol], C7-C9-alkyl-3-[3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxyphenyl]propion ether, sesqui(benzotriazolyl-tert-butylhydroxyphenylpropionate)PEG-6, 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-(2'-hydroxy-3'-t-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2,4- Di-tert-butyl-6-(5-chloro-2H-1,2,3-benzotriazol-2-yl)phenol, 2-(2H-benzo[d][1,2,3]triazol-2-yl)-6-(2-phenylpropan-2-yl)-4-(2,4,4-trimethylpentan-2-yl)phenol, 2-(5-tert-butyl-2-hydroxyphenyl)benzotriazole, 2-(5-chloro-2H-benzotriazol-2-yl)-4-methyl-6-tert-butylphenol, 2-[2-hydroxy-3-tert-butyl-5-[2-(octyloxycarbonyl)ethyl]phenyl]-2H-benzotriazole, 2,4-bis(α,α-dimethylbenzyl)-6-(2H-benzotriazol-2-yl)phenol, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, Tinuvin manufactured by BASF 970, UVA-903KT. The number after C indicates the number of carbon atoms. PEG stands for polyethylene glycol.

[0023] Examples of benzophenone-based UV absorbers include 2,2',4,4'-tetrahydroxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, and UVA-935LH manufactured by BASF.

[0024] An example of the azomethine UV absorber is BONASORB UA-3701 manufactured by Orient Chemical Industries Co., Ltd. Examples of indole-based UV absorbents include BONASORB UA-3911 and BONASORB UA-3912 manufactured by Orient Chemical Industry Co., Ltd.

[0025] An example of a benzodithiol UV absorber is 1,2-dibutyl-4-(4,7-dihydroxy-1,3-benzodithiol-2-ylidene)pyrazolidine-3,5-dione. An example of an oxazolone UV absorber is 2-methyl-41 benzylidene-5-oxazolone.

[0026] The organic UV absorbents may be used alone or in combination of two or more. As the organic UV absorbent, among the above, at least one selected from the group consisting of triazine-based UV absorbents, benzotriazole-based UV absorbents, and benzophenone-based UV absorbents is preferred, from the viewpoints of relatively low yellowness, high visible light transmittance, and excellent weather resistance, with benzophenone-based UV absorbents being more preferred, and 2,2',4,4'-tetrahydroxybenzophenone being particularly preferred.

[0027] The content of organic UV absorber in the UV shielding film is t1×c1 / 100, which will be described later, of 5.0×10 -6The content of the organic UV absorbent in the UV shielding film is preferably 2% by mass or more, more preferably 10% by mass or more, particularly preferably 15% by mass or more, and preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less, and particularly preferably 30% by mass or less, based on the total mass of the UV shielding film. When the content of the organic UV absorbent is equal to or more than the lower limit, the UV shielding performance is excellent, and when the content is equal to or less than the upper limit, the decrease in visible light transmittance and bleeding out of the UV absorbent can be suppressed. The lower limit and the upper limit can be appropriately combined.

[0028] In the UV shielding film, the organic UV absorber may be dissolved in the matrix in molecular units or may be dispersed in the form of particles.

[0029] When the organic UV absorber is dispersed in the matrix in the form of particles, the average particle size of the organic UV absorber in the UV shielding film is preferably 200 nm or less, more preferably 100 nm or less, and particularly preferably 50 nm or less. When the average particle size is equal to or less than the upper limit, the haze of the UV shielding film can be reduced and the lateral visible light transmittance can be increased. The lower limit is not particularly limited, but is, for example, 5 nm. The average particle size of the organic UV absorber in the UV shielding film is measured by cross-sectional observation using an electron microscope.

[0030] The organic UV absorber may be bonded to other components in the UV shielding film (matrix, additives other than UV absorbers, etc.). When the organic UV absorber is bonded to other components, the organic UV absorber can be prevented from precipitating (bleeding out) on the surface of the UV shielding film.

[0031] The matrix is ​​formed from a matrix material. The matrix may be a cured or solidified product of the matrix material. Examples of the matrix material include a curable silane compound, an acrylic compound, and the like. The matrix material may be used alone or in combination of two or more kinds. The matrix material preferably contains a curable silane compound in terms of excellent scratch resistance of the UV shielding film. The matrix preferably contains silica, which provides the UV blocking film with excellent scratch resistance.

[0032] The content of the curable silane compound or its cured product in the UV shielding film is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, even more preferably 50% by mass or more, particularly preferably 60% by mass or more, most preferably 70% by mass or more, and also preferably 98% by mass or less, more preferably 90% by mass or less, particularly preferably 85% by mass or less, based on the total mass of the UV shielding film. When the content of the curable silane compound or its cured product is the lower limit or more, the durability of the UV shielding film is excellent. When the content of the curable silane compound or its cured product is the upper limit or less, the UV shielding film is unlikely to crack or peel off. The lower limit and the upper limit can be appropriately combined.

[0033] The curable silane compound is preferably a compound having one or more reactive silyl groups, more preferably a compound having two or more reactive silyl groups. When the reactive silyl group is a hydrolyzable silyl group, a silanol group is generated by hydrolysis reaction. The silanol groups (silanol groups as reactive silyl groups or silanol groups generated from hydrolyzable silyl groups) undergo a dehydration condensation reaction with each other to cure. The curable silane compound may be a partial condensate of a compound having two or more reactive silyl groups. The partial condensate is a polymer generated by a dehydration condensation reaction of a part of the reactive silyl groups of the compound. The upper limit of the number of reactive silyl groups that the curable silane compound has is not particularly limited, but in the case of a curable silane compound other than a partial condensate, the upper limit is, for example, 10.

[0034] The hydrolyzable silyl group is typically a group in which at least a portion of the hydrogen atoms of a silyl group (-SiH3) is substituted with a hydrolyzable group. A portion of the hydrogen atoms may be substituted with a substituent other than the hydrolyzable group. The hydrolyzable group is a group that can be hydrolyzed to a hydroxyl group. Examples of the hydrolyzable group include an alkoxy group, an aryloxy group, a halogen atom, an acyl group, an acyloxy group, and an isocyanato group (-NCO). Examples of the alkoxy group include an alkoxy group having 1 to 4 carbon atoms. From the viewpoint of long-term storage stability, an ethoxy group is more preferable, and from the viewpoint of shortening the hydrolysis reaction time, a methoxy group is more preferable. Examples of the halogen atom include a chlorine atom. Examples of the acyl group include an acyl group having 1 to 6 carbon atoms. Examples of the acyloxy group include an acyloxy group having 1 to 6 carbon atoms. As the hydrolyzable group, an alkoxy group or a halogen atom is preferred from the viewpoint of ease of synthesis. As the alkoxy group, an alkoxy group having 1 to 4 carbon atoms is preferred from the viewpoint of excellent storage stability of the curable silane compound and suppression of outgassing during reaction, an ethoxy group is more preferred from the viewpoint of long-term storage stability, and a methoxy group is more preferred from the viewpoint of shortening the hydrolysis reaction time. As the halogen atom, a chlorine atom is preferred. Examples of the substituent other than the hydrolyzable group include a hydroxyl group and a siloxane skeleton-containing group (for example, X b2 ), a hydrocarbon chain-containing group (e.g., X b3 ) are mentioned.

[0035] Examples of the curable silane compound include a compound represented by the following formula X1, a compound represented by the following formula X2, a compound having a reactive silyl group and a specific functional group (epoxy group, (meth)acryloyl group, vinyl group, isocyanato group), and a partial condensate thereof. "(Meth)acryloyl" refers to acryloyl or methacryloyl. The partial condensate may be formed from one type of compound or two or more types of compounds.

[0036] Si(X b1 ) m1 (X b2 ) m2 (X b3 ) m3 Formula X1 However, X b1 each independently represents a hydrolyzable group, X b2 each independently represents a siloxane skeleton-containing group, X b3 are each independently a hydrocarbon chain-containing group, m1 is an integer from 2 to 4; m2 and m3 each independently represent an integer of 0 to 2, and m1+m2+m3 is 4. In addition, X b1 , X b2 , X b3 each bond to Si in the formula.

[0037] X b2 Examples of the group include a dimethylsiloxane skeleton-containing group. X b3 Examples of the alkyl group include an alkyl group and an aryl group. The alkyl group may be linear or branched. The number of carbon atoms in the alkyl group is, for example, 1 to 18. Examples of the aryl group include a phenyl group. The compound represented by formula X1 is preferably a compound in which m1 is 4, m2 and m3 are 0, or a compound in which m1 is 3, m2 is 0, and m3 is 1, more preferably a compound represented by any one of formulas X1-1 to X1-5 below, and even more preferably a compound represented by formula X1-1 or formula X1-2. The compound represented by formula X1-1 or formula X1-2 is preferably tetraethoxysilane, tetramethoxysilane, or triethoxymethylsilane.

[0038] Si(X b1 )4 type X1-1 CH3-Si(X b1 )3 type X1-2 C2H5-Si(X b1 )3 type X1-3 n-C3H7-Si(X b1 )3 type X1-4 (CH3)2CH-Si(X b1 )3 type X1-5

[0039] (X b6 )3Si-Y b1 -Si(X b7 )3 type X2 However, X b6 and X b7 each independently represents a hydrolyzable group or a hydroxyl group, Y b1 is a divalent organic group.

[0040] In formula X2, Y b1 is a divalent organic group that connects the reactive silyl groups at both ends. Y b1 The carbon number is preferably 1 to 8, and more preferably 1 to 3. Y b1 Examples of the alkylene group include an alkylene group having an etheric oxygen atom between carbon atoms, and a phenylene group. Examples include -CH2CH2-, -CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2CH2-, -CH2C(CH3)2CH2-, -C(CH3)2CH2CH2C(CH3)2-, -CH2CH2OCH2CH2-, -CH2CH2CH2OCH2CH2CH2-, -CH(CH3)CH2OCH2CH(CH3)-, and -CH4-. Examples of compounds represented by formula X2 include (CH3O)3Si(CH2)2Si(OCH3)3, (C2H5O)3Si(CH2)2Si(OC2H5)3, (OCN)3Si(CH2)2Si(NCO)3, Cl3Si(CH2)2SiCl3, (CH3O)3Si(CH2)6Si(OCH3)3, and (C2H5O)3Si(CH2)6Si(OC2H5)3.

[0041] When the curable silane compound contains a compound having a reactive silyl group and a specific functional group, the UV absorber can be immobilized in the matrix. An example of the compound having a reactive silyl group and a specific functional group is a compound represented by the following formula X3. Z b1 -Y b2 -Si(X b11 ) m4 (X b12 ) m5 (X b13 ) m6 formula x3 However, X b11 are each independently a hydrolyzable group, X b12 each independently represents a siloxane skeleton-containing group, X b13 are each independently a hydrocarbon chain-containing group, m4 is an integer from 1 to 3; m5 and m6 each independently represent an integer of 0 to 2, and m4 + m5 + m6 is 3; Z b1 is a specific functional group, Y b2 is a single bond or a divalent organic group. In addition, X b11 , X b12 , X b13 each bond to Si in the formula.

[0042] Examples of the compound having a reactive silyl group and an epoxy group include (3-glycidyloxypropyl)trimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. Examples of commercially available products include KBM-403 manufactured by Shin-Etsu Chemical Co., Ltd.

[0043] Examples of the compound having reactive silyl group and (meth)acryloyl group include 3-acryloyloxypropyl trimethoxysilane, 3-acryloyloxypropyl triethoxysilane, 3-acryloyloxypropyl dimethoxysilane, 3-acryloyloxypropyl diethoxysilane, 3-acryloyloxypropyl monomethoxysilane, 3-acryloyloxypropyl monoethoxysilane, 3-methacryloyloxypropyl trimethoxysilane, 3-methacryloyloxypropyl triethoxysilane, 3-methacryloyloxypropyl dimethoxysilane, 3-methacryloyloxypropyl diethoxysilane, 3-methacryloyloxypropyl monomethoxysilane, and 3-methacryloyloxypropyl monoethoxysilane. Examples of commercially available products include KBM-5103 and KBE-502 manufactured by Shin-Etsu Chemical Co., Ltd.

[0044] Examples of compounds having a reactive silyl group and a vinyl group include vinyltriethoxysilane, vinyltrimethoxysilane, vinyldiethoxysilane, vinyldimethoxysilane, vinylmonoethoxysilane, and vinylmonomethoxysilane. Examples of commercially available products include KBE-1003 manufactured by Shin-Etsu Chemical Co., Ltd.

[0045] Examples of compounds having a reactive silyl group and an isocyanato group include 3-isocyanatepropyltriethoxysilane, 3-isocyanatepropyldiethoxysilane, 3-isocyanatepropylmonoethoxysilane, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyldimethoxysilane, and 3-isocyanatepropylmonomethoxysilane. Examples of commercially available products include KBE-9007N manufactured by Shin-Etsu Chemical Co., Ltd.

[0046] The curable silane compounds may be used alone or in combination of two or more. For example, the compound represented by formula X2 may be used in combination with a curable silane compound other than the compound represented by formula X2 as the curable silane compound. In this case, the mass ratio of the compound represented by formula X2 to the total of the curable silane compounds other than the compound represented by formula X2 is preferably 0.05 to 0.2, more preferably 0.054 to 0.15, and particularly preferably 0.06 to 0.13. When the mass ratio is equal to or greater than the lower limit of the above range, the UV shielding film has excellent alkali resistance. When the mass ratio is equal to or less than the upper limit of the above range, the UV shielding film has high hardness and excellent abrasion resistance and scratch resistance.

[0047] It is also preferable to use in combination a compound having a reactive silyl group and a specific functional group with a compound in which m1 in formula X1 is 4, m2 and m3 are 0. In this case, the mass ratio of the compound having a reactive silyl group and a specific functional group to the compound in which m1 in formula X1 is 4, m2 and m3 are 0 is preferably 0.5 to 3.0, more preferably 0.8 to 2.0, and particularly preferably 1.0 to 1.5.

[0048] The mass ratio of the curable silane compound to the UV absorbent is preferably 0.5 to 35, more preferably 0.6 to 15, and particularly preferably 2 to 5. When the mass ratio is equal to or more than the lower limit, the UV absorbent can be uniformly dispersed in the UV shielding film. When the mass ratio is equal to or less than the upper limit, the hardness of the UV shielding film is increased, and the abrasion resistance and scratch resistance are excellent.

[0049] The UV shielding film may further contain other components (excluding the liquid medium) other than the UV absorber and the matrix material, such as a resin (excluding the matrix material), a surface conditioner, and a catalyst.

[0050] If the UV blocking film contains a resin, the occurrence of cracks can be suppressed. Examples of the resin include epoxy resin, acrylic resin, fluororesin, and silicone resin. These resins may be used alone or in combination of two or more. The content of the resin in the UV shielding film is preferably from 1 to 15 mass %, more preferably from 3 to 10 mass %, and still more preferably from 5 to 10 mass %, based on the total mass of the UV shielding film.

[0051] When the UV screening film contains a surface conditioner, the occurrence of orange peel and the like during the formation of the UV screening film is suppressed, and a good appearance is obtained. Examples of the surface conditioner include the BYK series (BYK300, 307, etc.) manufactured by BYK-Chemie. The content of the surface conditioner is preferably from 0.1 to 1 mass %, and more preferably from 0.2 to 0.7 mass %, relative to the UV shielding film.

[0052] Examples of the catalyst include an acid catalyst, a base catalyst, and a silylation catalyst. The acid catalyst and the base catalyst each function as a catalyst for the curing reaction of the curable silyl compound (hydrolysis reaction of hydrolyzable groups, condensation reaction between hydroxyl groups bonded to silicon atoms). Examples of the acid catalyst include acetic acid, nitric acid, hydrochloric acid, maleic acid, polymaleic acid, sulfuric acid, nitric acid, hydrochloric acid, acetic acid, formic acid, phthalic acid, and malic acid. Examples of the base catalyst include ammonia, sodium hydroxide, potassium hydroxide, and amine catalysts such as triethylamine. As a catalyst for the curing reaction of the curable silyl compound, an acid catalyst is preferred in terms of excellent hydrolysis rate.

[0053] The silylation catalyst functions as a catalyst for the reaction (silylation reaction) between a compound having the above-mentioned reactive silyl group and a specific functional group and a UV absorbent. As the silylation catalyst, for example, a quaternary ammonium salt as described in JP-A-58-10591 is preferable. As the quaternary ammonium salt, for example, tetramethylammonium chloride, tetraethylammonium chloride, benzyltrimethylammonium chloride, and benzyltriethylammonium chloride can be mentioned. An acid catalyst or a base catalyst may be used in combination with a silylation catalyst.

[0054] The product of the thickness t1 (cm) of the UV blocking film and the content c1 (mass%) of the UV absorber in the UV blocking film divided by 100 (t1 × c1 / 100) is 5.0 × 10 -6 That is 6.0 x 10 -6 More than 1.0×10 is preferable.-5 More preferably, 2.0×10 -5 More than 1.0×10 is particularly preferable. -2 Less than 5.0×10 is preferable. -3 Less than 1.0×10 is preferable. -3 The following is particularly preferred. When t1×c1 / 100 is equal to or greater than the lower limit, UV degradation of the drug can be suppressed, and the drug has excellent storage stability. When t1×c1 / 100 is equal to or less than the upper limit, the side visible light transmittance can be easily set to the preferred lower limit or more.

[0055] The thickness of the UV shielding film is t1×c1 / 100 = 5.0×10 -6 The thickness of the UV shielding film is preferably 0.3 to 10.0 μm, more preferably 0.6 to 5.0 μm, and particularly preferably 1.0 to 3.0 μm. When the thickness of the UV shielding film is equal to or greater than the lower limit, peeling of the UV shielding film when an external force such as scratching is applied can be suppressed. When the thickness of the UV shielding film is equal to or less than the upper limit, the occurrence of cracks can be suppressed. The thickness of the UV blocking film is a value measured at the position of the body of the container body. The method for measuring the thickness of the UV blocking film is as described in the Examples below.

[0056] It is preferable that the UV shielding film satisfies the following formula 1. Satisfying formula 1 indicates that the lateral UV transmittance of the UV shielding film alone is 50% or less. When the UV shielding film satisfies formula 1 below, it is easy to make the lateral UV transmittance of the medical glass container equal to or less than the above-mentioned preferable upper limit. The value of the right side of formula 1 is preferably 0.5, more preferably 0.3, further preferably 0.15, and particularly preferably 0.05. The smaller the value of the right side of formula 1, the more preferable it is, and there is no particular lower limit.

[0057]

number

[0058] In formula 1, x represents any wavelength in 5 nm intervals within the wavelength range of 300 to 380 nm, TGx represents the transmittance of the container body at wavelength x measured at the body position; Bx is a weighting coefficient at wavelength x shown in Table 1, Ax represents the absorbance at wavelength x measured with a path length of 1 cm for a solution or dispersion in which a UV absorber is dissolved or dispersed at a concentration of 10 ppm in a solvent or dispersion medium such as methanol, L is the thickness of the UV-shielding film measured at the body position [cm], C indicates the content [mass %] of the UV absorber in the UV shielding film.

[0059] [Table 1]

[0060] It is preferable that the UV shielding film satisfies the following formula 2. Satisfying formula 2 indicates that the lateral visible light transmittance of the UV shielding film alone is 60% or more. When the UV shielding film satisfies formula 2 below, it is easy to make the lateral visible light transmittance of the medical glass container equal to or higher than the preferable lower limit value described above. The value of the right side of formula 2 is preferably 0.6, more preferably 0.8, and particularly preferably 0.9. The larger the value of the right side of formula 2, the more preferable it is, and there is no particular upper limit.

[0061]

number

[0062] In formula 2, y represents an arbitrary wavelength in 10 nm intervals within the wavelength range of 380 to 780 nm, TGy represents the transmittance of the container body at wavelength y measured at the body position, By is a weighting coefficient at wavelength y shown in Table 2, Ay represents the absorbance at wavelength y measured with a path length of 1 cm for a solution or dispersion in which a UV absorber is dissolved or dispersed at a concentration of 10 ppm in a solvent or dispersion medium such as methanol, L is the thickness of the UV-shielding film measured at the body position [cm], C indicates the content [mass %] of the UV absorber in the UV shielding film.

[0063] [Table 2]

[0064] It is preferable that the UV shielding film satisfies the above formula 1 and also satisfies the above formula 2.

[0065] (Method of manufacturing medical glass containers) An example of a method for manufacturing the medical glass container of the first embodiment is a method in which a composition containing a UV absorber and a matrix material (hereinafter also referred to as a "UV shielding film-forming composition") is applied to at least the outer surface of the barrel of the container body to form a UV shielding film. As described above, in this embodiment, the UV absorbent is composed of at least one organic ultraviolet absorbent selected from the group consisting of triazine UV absorbents, benzotriazole UV absorbents, benzophenone UV absorbents, azomethine UV absorbents, indole UV absorbents, benzodithiol UV absorbents, and oxazolone UV absorbents. In addition, the product of the thickness t1 (cm) of the UV shielding film to be formed and the content c1 (mass%) of the UV absorbent in the UV shielding film divided by 100 (t1×c1 / 100) is 5.0×10 -6 That is all.

[0066] The composition for forming a UV shielding film may contain a liquid medium. When the composition for forming a UV shielding film contains a liquid medium, the composition for forming a UV shielding film can be applied by a wet application method. Examples of the liquid medium include an aqueous medium and an organic solvent. The aqueous medium may be water or a mixture of water and an organic solvent. The organic solvent in the aqueous medium may be any solvent that is miscible with water, and examples of the organic solvent include alcohol solvents such as methanol and ethanol, ester solvents such as butyl acetate and propylene glycol monomethyl ether acetate, and ketone solvents such as methyl ethyl ketone and cyclohexanone.

[0067] The composition for forming a UV shielding film may further contain other components in addition to the UV absorber, the matrix material, and the liquid medium, such as a resin (excluding the matrix material), a surface conditioner, and a catalyst. Each of these components is as described above.

[0068] When the matrix material contains a curable silane compound, the composition for forming a UV shielding film preferably contains a catalyst and an aqueous medium in addition to the UV absorber and the curable silane compound. The catalyst preferably contains an acid catalyst or a base catalyst. When the curable silane compound contains a functional group-containing silane compound, the catalyst preferably contains an acid catalyst or a base catalyst, and a silylation catalyst.

[0069] The composition can be prepared by mixing the UV absorber, the matrix material, and optionally the liquid medium and other components. The order of mixing the materials is not particularly limited.

[0070] An example of a method for preparing the composition will be described below, taking as an example a case where the composition contains, as a curable silane compound, a compound represented by formula X1 and a compound having a reactive silyl group and a specific functional group. First, a UV absorbent, a compound having a reactive silyl group and a specific functional group, a silylation catalyst, and an organic solvent are mixed and reacted under stirring. The reaction conditions are, for example, 80 to 120°C and 1 to 10 hours. This produces a preparation containing a reaction product of the UV absorbent and the compound having a reactive silyl group and a specific functional group. Next, water, an organic solvent, a compound represented by formula X1, an acid catalyst or a base catalyst, and other components as necessary are added to the obtained preparation liquid, and reacted under stirring. The reaction conditions are, for example, 20 to 60°C and 0.5 to 20 hours. In this way, a composition containing a hydrolysis partial condensate of the reactant and the compound represented by formula X1 is obtained.

[0071] The composition may be applied by a known method, such as dip coating, spray coating, flow coating, squeegee coating, sponge coating, or brush coating. In terms of excellent uniformity of the coating film, the dip coating method is preferred. After application, the coating of the composition is dried as necessary, for example, to cure the curable silane compound or to remove the liquid medium. Drying conditions can be appropriately selected depending on the purpose. For example, when the purpose is to cure the curable silane compound, conditions of 50 to 250°C and 10 seconds to 120 minutes can be mentioned.

[0072] The method for producing a medical glass container according to this embodiment is not limited to the method described above. For example, a resin may be used in place of the curable silane compound. A film containing a UV absorbent may be prepared in advance and laminated on the outer surface of the container body.

[0073] (Application) The medical glass container of the first embodiment is used for packaging medicine. The packaging method can be a known method depending on the shape of the container body. For example, in the case of the medical glass container 100 shown in Fig. 1, the medicine is placed in the glass vial 10 through the opening of the mouth part 15, and the opening is sealed with a rubber stopper or the like. A package in which a drug is packed in a medical glass container is typically stored in a self-supporting state with the bottom of the container body facing down.

[0074] The drug is not particularly limited, and may be any drug that is conventionally contained in a glass packaging container such as a glass vial or a glass ampoule. The drug contains an active ingredient. The active ingredient contained in the drug may be one type or two or more types. The drug may further contain ingredients other than the active ingredient. Examples of ingredients other than the active ingredient include a liquid medium and an excipient. The medicine may be in a solid form (tablets, granules, powder, capsules, etc.) or liquid form at room temperature (e.g., 15 to 30° C.). In view of the great advantages of medical glass containers in terms of excellent storage stability, visibility, and operability of medicines, the medicine is preferably a liquid composition containing an active ingredient and a liquid medium.

[0075] The drug preferably contains an antibody-drug conjugate (hereinafter also referred to as "ADC") as an active ingredient. ADC has low storage stability in conventional glass packaging containers. According to the medical glass container of this embodiment, ADC can be stored with good storage stability. Examples of ADCs include trastuzumab and gemtuzumab ozogamicin.

[0076] Second Embodiment The medical glass container according to the second embodiment comprises a glass container body in which medicine is contained, the glass container body having a bottom and a body rising from the periphery of the bottom, and a UV-shielding film covering the surface of the container body at least in the body. The medical glass container according to the second embodiment is the same as the first embodiment except for the UV shielding film, and the preferred ranges of the side UV transmittance, side visible light transmittance, and side YI of the medical glass container are also the same.

[0077] (UV shielding film) In the second embodiment, the UV shielding film contains only metal oxide particles as a UV absorbent. Examples of metal oxides constituting the metal oxide particles include zinc oxide, titanium oxide, cerium oxide, iron oxide, and tungsten oxide. Zinc oxide and titanium oxide are preferred because they have high UV absorbance, low visible light absorbance relative to UV absorbance, and little yellowness.

[0078] The average particle size of the metal oxide particles is preferably 500 nm or less, more preferably 300 nm or less, even more preferably 200 nm or less, particularly preferably 100 nm or less, most preferably 50 nm or less, and preferably 1 nm or more, more preferably 3 nm or more, particularly preferably 10 nm or more. When the average particle size is the upper limit or less, the haze can be reduced, and the visibility and operability are improved. When the average particle size is the lower limit or more, the ultraviolet absorbing performance is improved. The upper limit and the lower limit can be appropriately combined. The average particle size of the metal oxide particles is measured by a dynamic light scattering method.

[0079] The content of metal oxide particles in the UV shielding film is t2×c2 / 100, which will be described later, is 1.78×10 -5 ~1.18×10 -3 The content of the metal oxide particles in the UV shielding film is preferably 10% by mass or more, more preferably 15% by mass or more, particularly preferably 20% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, particularly preferably 30% by mass or less, based on the total mass of the UV shielding film. When the content of the metal oxide particles is equal to or more than the lower limit, the UV shielding performance is excellent, and when the content is equal to or less than the upper limit, the decrease in visible light transmittance can be suppressed. The lower limit and the upper limit can be appropriately combined.

[0080] UV blocking films typically contain a UV absorber in a matrix. The type of matrix is ​​the same as in the first embodiment.

[0081] The content of the curable silane compound or its cured product in the UV shielding film is preferably 20% by mass or more, more preferably 30% by mass or more, particularly preferably 35% by mass or more, and preferably 90% by mass or less, more preferably 80% by mass or less, particularly preferably 70% by mass or less, based on the total mass of the UV shielding film. When the content of the curable silane compound or its cured product is equal to or more than the lower limit, the durability of the UV shielding film is excellent. When the content of the curable silane compound or its cured product is equal to or less than the upper limit, the UV shielding film is unlikely to crack or peel off. The lower limit and the upper limit can be appropriately combined.

[0082] The mass ratio of the curable silane compound to the UV absorbent is preferably 0.1 to 10, more preferably 0.3 to 5, and particularly preferably 0.5 to 3. When the mass ratio is equal to or greater than the lower limit, the UV absorbent can be uniformly dispersed in the UV shielding film. When the mass ratio is equal to or less than the upper limit, the UV shielding film has high hardness and excellent abrasion resistance and scratch resistance.

[0083] The UV shielding film may further contain other components (excluding the liquid medium) other than the UV absorber and the matrix material, such as a resin (excluding the matrix material), a surface conditioner, a catalyst, and a dispersant. The resin, surface conditioner, and catalyst may be the same as those in the first embodiment.

[0084] The content of the resin in the UV shielding film is preferably from 3 to 30 mass %, more preferably from 5 to 25 mass %, and particularly preferably from 10 to 20 mass %, based on the total mass of the UV shielding film.

[0085] The content of the surface conditioner is preferably from 0.1 to 1 mass %, more preferably from 0.2 to 0.5 mass %, based on the UV screening film.

[0086] The dispersant is used to improve the dispersion stability of the metal oxide particles in the composition that forms the UV screening film. An example of the dispersant is Sisperbyk 180 manufactured by BYK-Chemie. The content of the dispersant is, for example, 1 to 100% by mass relative to the metal oxide particles.

[0087] The product of the thickness t2 (cm) of the UV blocking film and the content c2 (mass%) of the UV absorber in the UV blocking film divided by 100 (t2 × c2 / 100) is 1.78 × 10 -5 That is 3.0 x 10 -5 More than 1.0×10 is preferable. -4 More than 1.18×10 is particularly preferable. -3 is less than or equal to 5.0 x 10 -4 Less than 3.0×10 is preferable. -4 The following is particularly preferred. When t2×c2 / 100 is equal to or greater than the lower limit, UV degradation of the drug can be suppressed, and the drug has excellent storage stability. When t2×c2 / 100 is equal to or less than the upper limit, the side visible light transmittance is easily set to the preferred lower limit or greater. The lower limit and upper limit can be appropriately combined.

[0088] The thickness of the UV shielding film is t2×c2 / 100 = 1.78×10 -5 ~1.18×10 -3 The thickness of the UV shielding film is preferably 0.4 to 30 μm, more preferably 0.5 to 20 μm, further preferably 0.8 to 10 μm, and particularly preferably 1.0 to 5.0 μm. When the thickness of the UV shielding film is equal to or greater than the lower limit, the UV shielding performance is excellent. When the thickness of the UV shielding film is equal to or less than the upper limit, the UV shielding film is easily adhered to the container body.

[0089] It is preferable that the UV shielding film satisfies the above formula 1. It is preferable that the UV shielding film satisfies the above formula 2. It is particularly preferable that the UV shielding film satisfies the above formula 1 and also satisfies the above formula 2.

[0090] (Method of manufacturing medical glass containers) The method for producing a medical glass container according to the second embodiment includes using only metal oxide particles as a UV absorbent, dividing the product of the thickness t2 (cm) of the UV shielding film to be formed and the content c2 (mass%) of the UV absorbent in the UV shielding film by 100 (t2×c2 / 100) by 1.78×10 -5 ~1.18×10 -3 Except for the above, the method for producing a medical glass container is the same as that of the first embodiment.

[0091] (Application) The applications of the medical glass container of this embodiment are similar to those of the medical glass container of the first embodiment.

[0092] Third Embodiment The medical glass container according to the third embodiment includes a glass container body having a bottom and a body rising from the periphery of the bottom, in which a medicine is contained.

[0093] The side UV transmittance of the medical glass container according to this embodiment is 50% or less, preferably 40% or less, more preferably 30% or less, even more preferably 15% or less, and particularly preferably 5% or less. When the side UV transmittance is equal to or less than the upper limit, the deterioration of the medicine contained in the container body due to UV can be suppressed, and the storage stability of the medicine is excellent. The lower the side UV transmittance, the more preferable, and the lower limit is not particularly limited.

[0094] The side visible light transmittance of the medical glass container according to this embodiment is 60% or more, preferably 70% or more, more preferably 80% or more, and particularly preferably 90% or more. When the side visible light transmittance is equal to or more than the lower limit, the state of the drug in the container body (for example, the presence or absence of aggregates in a liquid drug) can be easily visually confirmed from the outside. The higher the side visible light transmittance, the more preferable it is, and there is no particular upper limit.

[0095] The side YI of the medical glass container according to this embodiment is preferably 40 or less, more preferably 20 or less, even more preferably 10 or less, particularly preferably 5 or less, and most preferably 1 or less. When the side YI is equal to or less than the upper limit, the state of the drug in the container body (for example, the presence or absence of aggregates in a liquid drug) is easily visually observed from the outside. The lower the side YI, the better, and there is no particular limit to the lower limit.

[0096] An example of the medical glass container according to this embodiment is a medical glass container according to the first or second embodiment having a side UV transmittance of 50% or less and a side visible light transmittance of 60% or more. In the first or second embodiment, the side UV transmittance can be set to 50% or less and the side visible light transmittance to 60% or more by adjusting the value (t1×c1 / 100, t2×c2 / 100) obtained by dividing the product of the thickness (cm) of the UV shielding film covering the surface of the container body and the content (mass%) of the UV absorbent in the UV shielding film by 100. However, the medical glass container according to this embodiment is not limited to these. For example, the UV shielding film is not limited to those containing the above-mentioned organic UV absorber or metal oxide particles. For example, it may be a deposition film of metal oxide, may contain an organic UV absorber other than the above-mentioned organic UV absorber, or may contain an inorganic UV absorber other than metal oxide. Examples of inorganic UV absorbers other than metal oxide include metal sulfides and metal selenides. The container body may have a side UV transmittance of 50% or less and a side visible light transmittance of 60% or more. In this case, the medical glass container does not need to have a UV shielding film. As a method for making the container body have a side UV transmittance of 50% or less and a side visible light transmittance of 60% or more, for example, a method of kneading a UV absorber into the glass constituting the container body can be mentioned.

[0097] (Application) The applications of the medical glass container of this embodiment are similar to those of the medical glass container of the first embodiment. EXAMPLES

[0098] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention. Examples 1 to 32 are examples, and Examples 33 to 38 are comparative examples.

[0099] [Evaluation method] (UV shielding film thickness) The thickness of the UV-shielding film was measured at the body of the medical glass container. Specifically, the step created by scratching the UV-shielding film (the distance from the interface with the container body to the surface of the UV-shielding film) was measured with a stylus-type surface profiler, and this step was taken as the thickness of the UV-shielding film.

[0100] (Side of medical glass container YI) At the position of the body of the medical glass container, the tristimulus values ​​X, Y, and Z were obtained by the spectrophotometric colorimetry specified in JIS Z 8722: 2009. Using the obtained tristimulus values ​​X, Y, and Z, YI was calculated according to the formula specified in JIS K 7373: 2006, and this value was taken as the side YI.

[0101] (Side visible light transmittance of medical glass containers) The body of the medical glass container was cut out with a glass cutter, and the visible light transmittance of the cut glass piece was determined using SolidSpec-3700 / 3700 ​​DUV in accordance with JIS R 3106:1998, and this value was taken as the side visible light transmittance.

[0102] (UV transmittance on the side of medical glass containers) The body of the medical glass container was cut out with a glass cutter, and the UV transmittance of the cut glass piece was determined using SolidSpec-3700 / 3700 ​​DUV in accordance with ISO9050:2003, and this value was taken as the side UV transmittance.

[0103] (Storage stability) 100 mg of trastuzumab solution (10 mg / mL) was enclosed as a drug in a medical glass container. Next, a storage test was conducted in which the medical glass container containing the drug was left outside for 3 hours (sunny, average temperature 25°C, 10:00-13:00). Each drug was analyzed by HPLC before and after the storage test, and the ratio (V2 / V1) of the integral value V2 of the peak of the main component after the storage test to the integral value V1 of the same peak before the storage test was calculated, and the storage stability was evaluated according to the following criteria. A: V2 / V1 is over 90%. B: V2 / V1 is less than 85% to 90%. C: V2 / V1 less than 85%.

[0104] (Visibility) A fibrinogen solution (1 mg / mL) was enclosed as a drug in a medical glass container. Next, the medical glass container containing the drug was shaken at 1,000 rpm for 3 hours to generate white fibrinogen aggregates inside the medical glass container. After that, the inside of the medical glass container was visually observed from a position 30 cm horizontally away from the medical glass container, and the visibility was evaluated according to the following criteria. A: Almost all of the white aggregates are visible. B: Some white aggregates are visible. C: No white aggregates are visible.

[0105] (operability) 100 mg of trastuzumab solution (10 mg / mL) was enclosed as a drug in a medical glass container. Next, an operation was performed in which the entire amount of drug was extracted from the enclosed medical glass container with a syringe needle. After performing the same operation on each of five medical glass containers in total, the amount of drug remaining in each medical glass container (amount extracted) was measured, and the operability was evaluated based on the average value according to the following criteria. A: The average residual value is less than 5 mg. B: The average residual value is 5 mg or more but less than 10 mg. C: The average residual value is 10 mg or more.

[0106] [Materials used] (Borosilicate glass vials) NV-5 manufactured by Nichiden Rika Glass Co., Ltd. (outer diameter 23 mm, height 42 mm, thickness 1.5 mm, inner mouth diameter 12.5 mm, outer mouth diameter 19.5 mm, capacity 5 mm).

[0107] (UV absorber) Benzophenone-based UV absorber: 2,2,4,4-tetrahydroxybenzophenone (BASF, Uvinul 3050). Benzotriazole UV absorber: 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-methylphenol (BASF, Tinuvin 326). Triazine-based UV absorber: 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine (ADEKA Corporation, Adeka STAB LA-F70). Zinc oxide particles: ZnO nanoparticles, average particle size 20 nm (Sakai Chemical Industry Co., Ltd., Finex-50). Titanium oxide particles: TiO2 nanoparticles, average particle size 15 nm (manufactured by Sakai Chemical Industry Co., Ltd., STR-100N).

[0108] [Preparation of Coating Liquid] (Preparation Example 1) Into a 100 mL round-bottom flask were added 2.09 g of a benzophenone-based UV absorber, 5.24 g of (3-glycidyloxypropyl)trimethoxysilane (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.), 4.25 g of butyl acetate, and 0.03 g of benzyltriethylammonium chloride, and the mixture was stirred at 105° C. for 4 hours to obtain Preparation 1. Next, 34.04 g of methyl ethyl ketone, 9.24 g of methanol, 15.34 g of pure water, 12.40 g of tetraethoxysilane, 9.52 g of an aqueous acetic acid solution (90 mass%), 0.95 g of an epoxy resin (SR-SEP, manufactured by Sakamoto Pharmaceutical Industry Co., Ltd.), 0.17 g of an aqueous polymaleic acid solution (Nonpol PMA-50W, manufactured by NOF Corporation), 0.01 g of maleic acid, and 0.06 g of a surface conditioner (BYK307, manufactured by BYK-Chemie AG) were added to the prepared solution 1, and the mixture was stirred at 50° C. for 2 hours to obtain a coating solution 1. Table 3 shows the composition of the solid content of the coating liquid 1. In Table 3, the content of the curable silane compound is calculated as SiO2.

[0109] (Preparation Examples 2 to 5) Coating Liquids 2 to 5 were prepared in the same manner as in Preparation Example 1, except that the amounts of the UV absorber and the curable silane compound were changed so that the contents relative to the solid content of the coating liquid were the values ​​shown in Table 3.

[0110] (Preparation Example 6) Coating liquid 6 was prepared in the same manner as in Preparation Example 1, except that a benzotriazole-based UV absorber was used instead of the benzophenone-based UV absorber.

[0111] (Preparation Example 7) Coating liquid 7 was prepared in the same manner as in Preparation Example 1, except that a triazine-based UV absorber was used instead of the benzophenone-based UV absorber.

[0112] (Preparation Example 8) Zinc oxide particles, a dispersant (disperbyk180, manufactured by BYK-Chemie), a dispersion medium (Solmix AP-1, manufactured by Japan Alcohol Sales Co., Ltd.), and zirconia beads were added to a glass bottle and stirred using a paint shaker to obtain Preparation 2. Into another glass bottle, 4.46 g of tetraethoxysilane, 0.74 g of KBM-403 (manufactured by Shin-Etsu Chemical Co., Ltd.), 1.65 g of 1N nitric acid, 0.22 g of water, 11.15 g of Solmix AP-1 (manufactured by Japan Alcohol Sales Co., Ltd.), 1.77 g of methanol, and 0.01 g of a surface conditioner (manufactured by BYK-Chemie, BYK307) were added and stirred at 50° C. for 60 minutes to obtain Preparation 3. Into another glass bottle, 2.5 g of Preparation 2, 5.0 g of Preparation 3, and 2.5 g of Solmix AP-1 (manufactured by Japan Alcohol Sales Co., Ltd.) were added and stirred at 25° C. for 10 minutes to obtain Coating Solution 8.

[0113] (Preparation Examples 9-10) Coating solutions 9 to 10 were prepared in the same manner as in Preparation Example 8, except that titanium oxide particles were used instead of zinc oxide particles, and the amounts of the UV absorber and the curable silane compound relative to the solid content of the coating solution were changed so that they were the values ​​shown in Table 3.

[0114] [Examples 1-4, 9, 10, 34] Coating liquid 1 was applied to a borosilicate glass vial with its outer surface cleaned by dip coating. Specifically, the vial was immersed in coating liquid 1 from the bottom of the vial to the upper limit of the neck using a tabletop dip coater (DT-1500) manufactured by SDI Corporation, and pulled up at an adjusted pulling speed so as to obtain a predetermined film thickness. The vial coated with coating liquid 1 was then dried at 200°C for 30 minutes to form a UV-shielding film, and medical glass containers of Examples 1 to 4, 9, 10, and 34 were obtained. The faster the lifting speed, the thicker the UV blocking film that is formed tends to be.

[0115] [Examples 5-8, 11-32, 35-38] Except for using the coating liquid shown in Table 4 instead of Coating Liquid 1, the same procedures as in Examples 1 to 4, 9, 10 and 34 were carried out to obtain medical glass containers of Examples 5 to 8, 11 to 32 and 35 to 38.

[0116] Example 33 The borosilicate glass vial with its outer surface washed was used as the medical glass container of Example 33 as it was.

[0117] The evaluation results of each example of the medical glass container are shown in Table 4. In Table 4, "En" in the "Thickness [cm] × UV absorber content [%]" column is "× 10 -n " For example, "5.69E-06" means "5.69 x 10 -06 ". The composition of the solid content of the coating liquid used in each example can be regarded as the composition of the UV blocking film formed in each example.

[0118] [Table 3]

[0119] [Table 4]

[0120] The medical glass containers of Examples 1 to 32 were excellent in storage stability for medicines, and also had high transparency, visibility, and operability. On the other hand, the medical glass container of Example 33 having no UV-shielding film was inferior in storage stability of medicines. In a UV shielding film that contains only a specific organic UV absorber as a UV absorber, the product of the thickness of the UV shielding film and the content (%) of the UV absorber in the UV shielding film is 5.0 x 10 -6 The medical glass container of Example 34 having a thickness of less than 100 mm was inferior in storage stability of the drug. In a UV-shielding film that contains only metal oxide particles as a UV absorber, the product of the thickness of the UV-shielding film and the content (%) of the UV absorber in the UV-shielding film is 1.78 × 10 -5 The medical glass containers of Examples 35, 37 and 38 having a thickness of less than 100 mm were inferior in storage stability of drugs. In a UV-shielding film that contains only metal oxide particles as a UV absorbent, the product of the thickness of the UV-shielding film and the content (%) of the UV absorbent in the UV-shielding film is 1.18 × 10 -3 The medical glass container of Example 36 had low transparency, poor visibility and operability, and was unsuitable for medical use. [Industrial Applicability]

[0121] According to the present invention, it is possible to provide a medical glass container having excellent storage stability for medicines, a film for a medical glass container which can obtain a medical glass container having excellent storage stability for medicines, and a method for producing a medical glass container. [Explanation of symbols]

[0122] 10...glass vial (container body), 11...bottom, 12...body, 13...shoulder, 14...neck, 15...mouth, 20...UV shielding film (membrane), 100...medical glass container

Claims

1. The container has a glass container body in which a medicine is contained, the glass container body having a bottom and a body part rising from a peripheral edge of the bottom, and a film covering a surface of the container body at least in the body part, the film contains an ultraviolet absorber; the ultraviolet absorber is composed of at least one organic ultraviolet absorber selected from the group consisting of triazine-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, azomethine-based ultraviolet absorbers, indole-based ultraviolet absorbers, benzodithiol-based ultraviolet absorbers, and oxazolone-based ultraviolet absorbers; The product of the thickness t1 (cm) of the film and the content c1 (mass%) of the ultraviolet absorber in the film is divided by 100 (t1 × c1 / 100), which is 5.0 × 10 -6 That's it for medical glass containers.

2. 2. The medical glass container according to claim 1, wherein the thickness t1 of the film is 1.0 to 10.0 μm.

3. The container has a glass container body in which a medicine is contained, the glass container body having a bottom and a body part rising from a peripheral edge of the bottom, and a film covering a surface of the container body at least in the body part, the film contains an ultraviolet absorber; the ultraviolet absorber is composed only of metal oxide particles, The product of the thickness t2 (cm) of the film and the content c2 (mass%) of the ultraviolet absorber in the film is divided by 100 (t2×c2 / 100), which is 1.78×10 -5 ~1.18 x 10 -3 That is, a medical glass container.

4. 4. The medical glass container according to claim 3, wherein the thickness t2 of the film is 1.0 to 5.0 μm.

5. 4. The medical glass container according to claim 3, wherein the average particle size of the metal oxide particles is 1 to 500 nm.

6. The container has a glass body in which a medicine is contained, the glass body having a bottom and a body rising from a peripheral edge of the bottom, A medical glass container, wherein the ultraviolet light transmittance measured at the body is 50% or less, and the visible light transmittance measured at the body is 60% or more.

7. 7. The medical glass container according to claim 6, wherein the yellowness index measured at the body position is 20 or less.

8. The medical glass container according to any one of claims 1 to 7, wherein the container body is a glass vial.

9. The medical glass container according to any one of claims 1 to 7, wherein the drug comprises an antibody-drug conjugate.

10. Contains UV absorbers, the ultraviolet absorber is composed of at least one organic ultraviolet absorber selected from the group consisting of triazine-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, azomethine-based ultraviolet absorbers, indole-based ultraviolet absorbers, benzodithiol-based ultraviolet absorbers, and oxazolone-based ultraviolet absorbers; The product of the thickness t1 (cm) of the film and the content c1 (mass%) of the ultraviolet absorber in the film is divided by 100 (t1 × c1 / 100), which is 5.0 × 10 -6 That is all about the membrane for medical glass containers.

11. Contains UV absorbers, the ultraviolet absorber is composed only of metal oxide particles, The product of the thickness t2 (cm) of the film and the content c2 (mass%) of the ultraviolet absorber in the film is divided by 100 (t2×c2 / 100), which is 1.78×10 -5 ~1.18 x 10 -3 A membrane for medical glass containers.

12. 12. The film for medical glass containers according to claim 10, which is formed from a composition containing the ultraviolet absorber and a matrix material.

13. A method for producing a medical glass container, comprising the steps of: applying a composition containing an ultraviolet absorber and a matrix material to at least a surface of a body of a glass container body in which a medicine is contained, the body having a bottom and a body rising from a peripheral edge of the bottom, to form a film; the ultraviolet absorber is composed of at least one organic ultraviolet absorber selected from the group consisting of triazine-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, azomethine-based ultraviolet absorbers, indole-based ultraviolet absorbers, benzodithiol-based ultraviolet absorbers, and oxazolone-based ultraviolet absorbers; The product of the thickness t1 (cm) of the film and the content c1 (mass%) of the ultraviolet absorber in the film is divided by 100 (t1 × c1 / 100), and the product is calculated as 5.0 × 10 -6 The above is a method for producing a medical glass container.

14. A method for producing a medical glass container, comprising the steps of: applying a composition containing an ultraviolet absorber and a matrix material to at least a surface of a body of a glass container body in which a medicine is contained, the body having a bottom and a body rising from a peripheral edge of the bottom, to form a film; the ultraviolet absorber is composed only of metal oxide particles, The product of the thickness t2 (cm) of the film and the content c2 (mass%) of the ultraviolet absorber in the film is divided by 100 (t2 × c2 / 100), which is 1.78 × 10 -5 ~1.18 x 10 -3 The method for manufacturing a medical glass container comprises the steps of:

15. The method for producing a medical glass container according to claim 13 or 14, wherein the matrix material comprises a curable silane compound, and the composition further comprises a catalyst and an aqueous medium.